Penggambaran feminisme seorang ibu dalam membangun kepribadian anaknya di film petualangan menangkap petir (Jurnal Kajian Media, 2020)
In the Adventure Film Catching Lightning there are several issues and concerns that want to be displayed through audio visual works. One example is about a mother (Beth) who strongly restrains her child and accentuates the feminism of the character of the mother (Beth) by prioritizing the perspective of the mother (Beth) in educating children, which is more prominent in the figure of the mother (Beth) than the father (Mahesa). In feminism itself, women really want to achieve gender equality, and from the observations in this film the perspective of the mother (Beth) is explored deeper, about how she thinks and behaves more prominent than some other adult male characters in the film this. A mother is generally very caring for children and wants to educate their children well, but many deviate from the goals of the mother herself which instead change from educating to obeying, and the figure of Mother (Beth) in this film tries to do that in which feminism here it is shown when Mother (Beth) collides with Father (Mahesa) or Grandfather where Mother (Beth) tries to keep arguing and does not want to obey just because they are Men or husband and tries to convey her mindset in educating children. Keywords: Feminism; Petulangan Menangkap Petir; Film; Film Characters.